Notes on Early Land Plants Today. 24. What is Protolophozia? (Cephaloziellaceae, Marchantiophyta) - Váňa, Jiří; Söderström, Lars; Hagborg, Anders; Von Konrat, Matt (Phytotaxa, 2013)
Protolophozia (Schuster 1968: 474) Schljakov (1979: 204) (≡ Lophozia subg. Protolophozia R.M.Schust.) is a segregate genus of Lophozia (Dumortier 1831: 53) Dumortier (1935: 17). It is mainly subantarctic and includes mostly rare species with narrow distribution ranges. Most of the species are not well known. The New Zealand species were described and discussed by Schuster (1968) and recently also by Engel & Glenny (2008) with overviews of known taxa by Schuster & Engel (1975) and Schuster (2002).